Enhancing Customer Experience in FinTech through AI, Machine Learning, and Data-Driven Insights - Nayak, Saugat (The Es Economics and Entrepreneurship, 2025)
This article discusses AI, ML, and data analyses to define how the FinTech sector enhances client experience. In the current digital financial service delivery world, customers expect to be offered efficient, customized, and self-service. FinTech companies meet these expectations through AI and ML technologies such as predictive analytics, natural language processing, recommendation systems, behavioral analytics, and real-time data visualization. These tools assist firms in creating customer-specific and user-specific CX and interactions to more effectively address customers and users, thus enhancing experience, contentment, and devotion. This article focuses on AI work in predictive customer life cycle management, real-time financial health monitoring, and better support systems. Furthermore, it highlights issues, including data privacy, AI model bias, regulatory issues, and technical issues that firms in this domain must overcome to offer secure and non-biased FinTech services. Conclusions based on the case studies and comparing existing industry trends investigate how the AI tools are being used in the real world to improve FinTech CX from companies such as Chime, Revolut, and Robinhood. In conclusion, with the future trends, the article indicates the potential expansion of AI and data-driven solutions in the FinTech CX, which will provide even more personalization, additional layers of fraud detection, and more mature predictions for the field of AI.